ENHANCING UNIVERSITY WEBSITE ASSOCIATED WITH CHATBOT SYSTEM: UTP STUDY CASE - Md Din, Nur Ain Fatehah (IRC, 2020)
Chatbots are commonly used in today’s business and operation. It is a program that mimics human language with the advancement of Artificial Intelligence (AI) and Machine Learning (ML). The chatbots are intended to be an ultimate virtual assistant that help the user to find information or completing tasks. There are many available open sources platform in order to develop the chatbot system. As for this project, the chatbot system will also be known as UTPbot. It will be implemented in the university official website to provide assistance for the users to find information and entertain any queries. Other than that, the chatbot is available for anyone who visit the university website anytime and anywhere. Microsoft Azure bot service, including Microsoft cognitive services, which is QnA Maker is used to develop UTPbot. The study of this project will cover on Universiti Teknologi Petronas (UTP) website system on the Admission part. The users can ask questions related to university and the chatbot will answer the particular queries immediately. The GUI of the chatbot is user-friendly and similar to Messaging Application.